Предмет: Алгебра,
автор: kislaya23
!!!!!!ПРЕОБРАЗУЙТЕ В МНОГОЧЛЕН ВЫРАЖЕНИЕ (u+3)(u+5)-(u+6)(u^2 -6u+36)
Ответы
Автор ответа:
0
(u+6)(u^2 -6u+36) = u³ + 6³ по формуле сокращенного умножения
(u+3)(u+5)-(u+6)(u^2 -6u+36) = u² + 5u + 3u + 15 - u³ - 216 =
= u² - u³ + 8u - 201
(u+3)(u+5)-(u+6)(u^2 -6u+36) = u² + 5u + 3u + 15 - u³ - 216 =
= u² - u³ + 8u - 201
Похожие вопросы
Предмет: Алгебра,
автор: dasssssha8
Предмет: Химия,
автор: Аноним
Предмет: Другие предметы,
автор: Mmadinaop27
Предмет: Математика,
автор: taisa3
Предмет: Математика,
автор: Аноним